Illiquidity and stock returns: Evidence from UK stock market over 1993 to 2008 - Wang, Shuyan (2009)
Illiquidity premium tend to be an interesting topic for both investors and academics. Previous researches suggest that less liquid assets provide higher returns. I examine whether there is evidence for the presence of illiquidity premium in UK stock market, using data for 447 companies in UK stock market from January 1993 to December 2008. Bid-ask spread and turnover rate are used as proxy for liquidity, and I examine illiquidity premium by time-series regression and cross-section regression respectively. Inconsistent with what has been document in many other studies, I do not find statistically significant illiquidity premium. By time-series regression approach, I find the evidence of modest but statistically insignificant illiquidity premium over 1-, 6-, and 12-month holding periods, using bid-ask spread as proxy for liquidity. By cross-section regression approach I find the presence of illiquidity premiums using turnover rate as the proxy for liquidity. The result indicates that a 1% decrease in turnover rate leads to a higher return of 0.23 basis points per month. However, this illiquidity premium is weak and again statistically insignificant. The negative and insignificant relation between turnover rate and stock returns persists after controlling for book-to-market ratio and firm size effect however it subjects to subperiod effect.